Meningkatkan Kreativitas Dan Motivasi Pembelajaran Matematika Menggunakan Model PBL, RME Dan Snowball Throwing Pada Kelas IV SD - Ari Chandra Setiawan (CV. ITTC INDONESIA, 2025)
This study aims to improve the learning outcomes of fourth-grade students at SDN Gambut 11 in fraction material through the implementation of Problem-Based Learning, Realistic Mathematics Education, and Snowball Throwing models. The research involved 30 students from the 2023/2024 academic year. Data were collected through observations of teacher and student activities, creativity, motivation, and written tests. The results showed significant improvement: teacher performance was rated “Very Good,” student activity “All Active,” creativity “Very High,” motivation “All High,” and learning outcomes achieved classical completeness.